Proceedings of the 10th International Workshop on Semantic Evaluation (SemEval-2016) 2016
DOI: 10.18653/v1/s16-1083
|View full text |Cite
|
Sign up to set email alerts
|

SemEval-2016 Task 3: Community Question Answering

Abstract: In this paper we propose a system for re-ranking answers for a given question. Our method builds on a siamese CNN architecture which is extended by two attention mechanisms. The approach was evaluated on the datasets of the SemEval-2017 competition for Community Question Answering (cQA), where it achieved 7 th place obtaining a MAP score of 86.24 points on the Question-Comment Similarity subtask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(104 citation statements)
references
References 36 publications
(32 reference statements)
0
104
0
Order By: Relevance
“…However, recent results have shown that automatically extracted large-scale lexicons (e.g., up to a million words and phrases) offer important performance advantages, as confirmed at shared tasks on Sentiment Analysis on Twitter at SemEval 2013-2016 [38,40,55,56]. Using such large-scale lexicons was crucial for the performance of the top-ranked systems.…”
Section: Sentiment Polarity Lexiconsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent results have shown that automatically extracted large-scale lexicons (e.g., up to a million words and phrases) offer important performance advantages, as confirmed at shared tasks on Sentiment Analysis on Twitter at SemEval 2013-2016 [38,40,55,56]. Using such large-scale lexicons was crucial for the performance of the top-ranked systems.…”
Section: Sentiment Polarity Lexiconsmentioning
confidence: 99%
“…The simplest and also the most popular task of sentiment analysis on Twitter is to determine the overall sentiment expressed by the author of a tweet [38,39,40,55,56]. Typically, this means choosing one of the following three classes to describe the sentiment: POSITIVE, NEGATIVE, and NEUTRAL.…”
Section: Variants Of the Task At Semevalmentioning
confidence: 99%
See 2 more Smart Citations
“…We show the results on two AS corpora, WikiQA and TREC13 (Wang et al, 2007). Then, we report the results obtained when using RelTextRank in a cQA system for English and Arabic comment selection tasks in the SemEval-2016 competition, Tasks 3.A and 3.D (Nakov et al, 2016).…”
Section: Previous Uses Of Reltextrankmentioning
confidence: 99%